ANALISIS FAKTOR-FAKTOR MAKROEKONOMI YANG MEMPENGARUHI INDEKS HARGA SAHAM GABUNGAN (IHSG) - Perdana, I Komang Rangga; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The capital market is very important for the economy of a country, because through buying and selling activities in the capital market can be known the purchasing power of investors or called investors which is often used as a benchmark for the economic condition of a country. Stocks are one of the capital market instruments that are growing among the people of Indonesia. In Indonesia, the state of the stock market composite stock price index (JCI). The movement of JCI is influenced by several domestic (internal) factors, including macroeconomic factors. The purpose of this study is to analyze the relationship of macroeconomic variables including Inflation, Exchange Rate, and Industrial Production Index (IPI) to JCI. This research was conducted in Indonesia. Data collection is carried out by documentation of secondary data from several related bodies as well as online sites. This study uses the Autoregressive Distributed Lag (ARDL) approach to look at the influence of Inflation, Exchange Rate, and Industrial Production Index (IPI) on JCI over time, as well as the influence of past JCI variables on present JCI. The results showed that Inflation and Exchange Rate had a significant influence on JCI and the Industrial Production Index (IPI) had no significant effect on JCI.